Perspectives on the psychological and emotional burden of having gestational diabetes amongst low-income women in Cape Town, South Africa - Lorrein Shamiso Muhwava; Katherine Murphy; Christina Zarowsky; Naomi Levitt (BMC, 2020)
Abstract Background The diagnosis of gestational diabetes mellitus (GDM) may affect women's mental wellbeing, functioning and quality of life, with potentially negative effects on treatment adherence. Identifying and addressing the psychological and emotional needs of women with GDM, could have benefits for sustainable long-term behavioural change following the affected pregnancy. This study explored the lived experiences of women with GDM and the impact of GDM on their experience of pregnancy and sense of well-being. Methods Purposive sampling was used to recruit women who had been diagnosed with GDM in their previous pregnancy and received antenatal care at a tertiary hospital in Cape Town, South Africa. This was a descriptive qualitative study using a combination of focus groups and in-depth interviews for an in- depth exploration of women's lived experiences of GDM, their context and perceived needs. Data analysis followed an iterative thematic analysis approach. Results Thirty-five women participated in nine focus groups and five in-depth interviews. Women discussed the emotional and psychological burden of having GDM, highlighting (i) their initial emotional reactions to receiving a GDM diagnosis, (ii) their experience of adjusting to the constraints of living with GDM (iii) their feelings of apprehension about childbirth and their maternal role and (iv) their feelings of abandonment in the post-partum period once the intensive support from both health system and family ends. Conclusions The current biomedical model used in the management of GDM, is highly foetal-centric and fails to acknowledge important psychological factors that contribute to women's overall wellbeing and experience of pregnancy. These results demonstrate the importance of incorporating mental health support in the management and care for women with GDM in public health services, along with facilitating emotional support from partners and family members. Based on our findings, we recommend routine mental health and psychosocial vulnerability screening and monitoring for women diagnosed with GDM throughout pregnancy and postpartum to improve prognoses.